Etileno e o florescimento de Coffea arabica: identificação in silico e análise da expressão gênica da via de biossíntese e sinalização em resposta ao déficit hídrico, reidratação e ação do 1-Metilciclopropeno - Santos, Iasminy Silva (2020)
Brazil is the largest producer and exporter of processed coffee in the world and based on the export volume forecast for 2020, those will continue. One of the most important t points is the coffee crop is the quality of beverage for the final consumer, and one of the most important factor influencing on the classification of the quality cup is the fruit ripening stage at the time of harvest. The degree of ripeness of the fruits is related to the flowering events that, in the coffee tree, can occur many times during the same production cycle. This sequential flowering results from the asynchronous development of the flower buds and is an intrinsic characteristic of coffee species, resulting in the uneven maturation of fruits. Drought periods accompanied by rain or irrigation to synchronize the flowering time of coffee tree have been reported, but the influence of these events on the internal processes that are involved in the induction and floral opening of Coffea arabica are not yet fully understood. It is known that during the water deficit changes at the cellular, molecular level occur to coordinate responses in unfavorable conditions. Plant hormones are involved in the quickly response to biotic and abiotic stresses, and ethylene is one of the plant hormones responsive to water deficit. Therefore, the influence of ethylene on coffee flowering was suggested based on the requirements for the floral buds development in coffee. In this sense, the observation of promoted anthesis by an ethylene action inhibitor was unexpected. 1-Methylcyclopropene (1-MCP) is widely marketed as an ethylene action antagonist, but when used in coffee plants showed a positive regulation of genes in the ethylene biosynthesis enzymes (ACS and ACO) and signaling (ETR4) of this hormone in. It was argued that the increase in ethylene biosynthesis may have raised the hormone levels and this would have regulated the opening time of coffee flowers. However, there is not consistent information on the changes in ethylene metabolism triggered by different water conditions and by 1-MCP. Aiming to increase knowledge about the influence of ethylene on the flowering of Coffea arabica, this study analyzed in silico possible genes orthologists from ACS and ACO, and analyzed the gene expression by RT-qPCR of eleven genes related to the biosynthesis and signaling pathways of ethylene in coffee trees submitted to different water treatments and treated with 1-MCP. The leaf water potential was evaluated during the experimental period, in addition to the quantification of ethylene production in each treatment. Coffea arabica has a small multigene family for the enzymes ACS and ACO. The level of expression of these homologous genes is regulated by the water condition and there is a unique and overlapping expression pattern in different organs. 1-MCP positively regulates the biosynthesis pathway by increasing the ethylene concentration in Coffea arabica leaves, possibly through a feedback mechanism due to the loss of negative feedback. However, 1-MCP suppresses the expression of the CaETR1-like receptor, possibly promoting a fine adjustment in sensitivity to ethylene.